Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMP Pada Materi Segiempat dan Segitiga - Puri Nur Aisyah; Siti umi Nur Khasanah; Anik Yuliani; Euis Eti Rohaeti (IKIP Siliwangi, 2018)
This study aims to determine the ability of solving mathematical problems of junior high school students in Kabupatan West Bandung with indicators of students' mathematical problem solving abilities that are used to identify known elements, questioned and adequacy of elements, selecting and implementing strategies to solve mathematical problems, interpret the results according to the initial problem , making a mathematical model of a situation or everyday problem, using mathematics meaningfully. This research was conducted to 31 students in one of Junior High School in Ngamprah Village, West Bandung Regency using qualitative descriptive method. Instruments used in the form of 5 items about students' mathematical problem solving abilities on the material quadrilateral and triangle with interviews to students. The conclusion of this research is the ability of mathematical problem solving of junior high school students in Ngamprah Village is still low.